ANALISIS PENGARUH KEPEMIMPINAN VISIONER, KOMUNIKASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BINTANG MANDIRI ABADI JAYA MEDAN - Susanto, Agus (UNIKA Santo Thomas, 2021)
This study aims to describe the effect of visionary leadership, communication and compensation on employee performance at PT. Bintang Mandiri Abadi Jaya Medan. This research was conducted for 7 (seven) months, start from February 2019 until August 2019. This research use descriptive and quantitative methods. The respondents of this research are all employee at PT. Bintang Mandiri Abadi Jaya Medan which amounted to 83 (eighty three) employee. The instrument is used a questionnaire to collent data from visionary leadership variable, communication variable, compensation variable and employee performance variable. Data analysis technique used is validity test, reliability test, descriptive analysis, normality test, heteroskedasticity test, multicolinearity test,multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test ot t test, simultaneous hypothesis test or f test, and calculation of coefficient of determination. The result of descriptive analysis for visionary leadership variable, communication variable, compensation variable and employee performance are in good category at PT. Bintang Mandiri Abadi Jaya Medan. Based on partial analysis, visionary leadership, communication and compensation have a positive and significant effect on employee performance at PT. Bintang Mandiri Abadi Jaya Medan. Simultaneously, visionary leadership, communication, compensation have a positive and significant influence on employee performance at PT. Bintang Mandiri Abadi Jaya Medan. The contribution of visionary leadership variable, communication variable and compensation variable to improve the employee performance variable is 0,805 or 80,5 %, while rest of 0,195 or 19,5 % influenced by other variable not examined by writer in this research, such as work commitment, work enviroment, work discipline, work motivation, job satisfaction and another else.